Systematic Literature Review: Students' Mathematical Representation Ability in Mathematics Learning - Youlanda L.Man; Mohammad Asikin; Sugiman Sugiman (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
The ability of mathematical representation in learning is very necessary, especially in learning mathematics. The purpose of this study was to examine the ability of students' mathematical representation in learning mathematics. Data is collected through related journals for review. The research method chosen in this study was to find the SRL (Systematic Literature Review) method. Data collection was carried out by documenting and reviewing all articles on mathematical representation abilities published in the period 2016-2021. The articles used in this study were 29 international journal articles indexed by Scopus and 31 nationally accredited which were obtained from the undergraduate google database using the publish or perish application. The ability of mathematical representation is very closely related to students, especially in learning mathematics, which is a form of interpretation of students' thoughts on problems that are used as tools to find solutions to mathematical problems.The results showed that the ability of mathematical representation in learning mathematics can be improved by providing innovations in learning and providing opportunities for students to develop mathematical representation skills by fulfilling the indicators of the mathematical representation itself. Thus the students' mathematical representation ability is no longer in the low category in solving mathematical problems.